2001
DOI: 10.1136/thorax.56.2.115
|View full text |Cite
|
Sign up to set email alerts
|

Role of bronchoalveolar lavage in immunocompromised patients with pneumonia treated with a broad spectrum antibiotic and antifungal regimen

Abstract: Background-In a retrospective study the value of bronchoalveolar lavage (BAL) in the diagnosis of pneumonia was investigated in 95 immunocompromised patients suVering from haematological disorders and receiving a regimen of broad spectrum antibiotics and antifungal agents (BSAR). Methods-With the exception of four afebrile patients, all had fever, raised C reactive protein (CRP) levels, and new infiltrates visible on chest radiography. All patients underwent BAL to identify the organism causing the pneumonia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
57
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 25 publications
(18 reference statements)
6
57
1
2
Order By: Relevance
“…When reported, FOB typically occurred 4 or more days following the initiation of empiric antibiotics. 11,12,25,27,28 Thus, our findings corroborate previous observations that link diagnostic delays to poor patient outcome and underscore the futility of late FOBguided antimicrobial adjustments in offsetting mortality among HSCT recipients with suspected pneumonia. A notable difference in our study compared with previousreports, however, is the significantly lower mortality rate associated with antibiotic modifications following early FOB.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…When reported, FOB typically occurred 4 or more days following the initiation of empiric antibiotics. 11,12,25,27,28 Thus, our findings corroborate previous observations that link diagnostic delays to poor patient outcome and underscore the futility of late FOBguided antimicrobial adjustments in offsetting mortality among HSCT recipients with suspected pneumonia. A notable difference in our study compared with previousreports, however, is the significantly lower mortality rate associated with antibiotic modifications following early FOB.…”
Section: Discussionsupporting
confidence: 81%
“…Our overall yield of 55% is notable in light of the near universal administration of antimicrobial therapy following HSCT, which may diminish the sensitivity and specificity of bronchoscopically obtained cultures. 12,17,21 We found that early FOBs were 2.5 times more likely to establish a diagnosis of pneumonia compared to late examinations (Po0.0001). Furthermore, early and late FOBs differed qualitatively in terms of responsible pathogens and resistance characteristics.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…5,8,22,23 Other studies have shown diagnostic yields of 51-80%. 3,19,[24][25][26] In total, 7 BALs were performed in children and contributed to the diagnosis in four of these. There are some difficulties associated with bronchoscopies in children, such as the frequent need for general anesthesia and difficulties in performing the procedure because of their small airways.…”
Section: Discussionmentioning
confidence: 99%